Ameliorative roles of compost on okra (Abelmoschus esculentus L.) exposed to drought stress at vegetative and reproductive growth stages (2020)
Okra growth and yield are adversely affected by drought at different growth stages. This is aggravated by poor soil fertility. In this study, the roles of compost applied at 0, 5 and 10 t/ha on the tolerance and morphophysiological response of okra (NHAe 47-4) exposed to varying levels of water stress (25%, 50%, 75% and 100% field capacity, FC), at different growth stages (vegetative, reproductive and vegetative-reproductive stages) for ten days duration were assessed. Data were collected on okra growth and yield, leaf relative water content (LRWC), leaf photosynthetic pigments (LPG) and proline accumulation. Results showed that drought stress reduced LRWC, LPG, growth and yield of Okra. This reduction was more evident in okra plants exposed to severe stress for 10 days and at the reproductive stage. Soil amendment with compost however, had cushioning effect on drought stressed okra. Compared to control, it increased the LRWC, LPG, growth and yield of okra. The ameliorative roles of compost were however, dependent on stress intensity, compost dosage, okra growth stage and stress duration. Though, okra plants stressed at 25% FC were more affected by drought stress, but compared to the un-amended soil, those grown on amended soil were more tolerant. Higher compost rate was superior to lower rates. Whereas, higher proline accumulation was recorded in plant exposed to 25% field capacity without amendment, proline accumulation was reduced in the plants grown on compost amended soil and exposed to drought which was an indication of stress reduction. Generally, okra stressed at vegetative growth stage only was able to recover rapidly and had better yield compared to those stressed at reproductive growth stage. It is concluded that addition of compost to soil could reduce the drought stress effect on okra.